Challenges in writing paragraph among pre-university EFL learners: Teachers' perceptions - الأمين أحمد محمد أحمد (الآداب للدراسات اللغوية والأدبية)
This study aims to investigate the Sudanese EFL teachers' perceptions about the challenges which face their learners in writing paragraph with reference to vocabulary and grammar. To achieve its objectives, the study applied the descriptive-analytical method, in which a questionnaire was used to address the research inquiries and goals. A total of 100 employed teachers participated in responding to the questionnaire. The study reported that the majority of Sudanese EFL teachers (93%) reported that their students in pre- university stage face difficulty to select appropriate words to convey their ideas clearly. In addition, 88% of the teachers reported that their students face grammar challenges affect the clarity while writing. They found it difficult to maintain the correct verb tenses throughout their paragraphs writing, as well as the using of complex sentence structures in English. Moreover, 90 % of the Sudanese EFL teachers indicated that their students find it helpful if their instructor provides feedback on their writing and support them with regular assign to improve their paragraph writing.